Development of gastric mucosa-associated microbiota in autoimmune gastritis with neuroendocrine tumors - Otani, Koji; Nakatsu, Geicho; Fujimoto, Kosuke; Miyaoka, Daichi; Sato, Noriaki; Nadatani, Yuji; Nishida, Yu; Maruyama, Hirotsugu; Ominami, Masaki; Fukunaga, Shusei; Hosomi, Shuhei; Tanaka, Fumio; et al. (Journal of gastroenterology, 2025)
Autoimmune gastritis (AIG) is a chronic atrophic gastritis that affects the gastric corpus, leading to achlorhydria, hypergastrinemia, and a precursor of neuroendocrine tumors (NETs). This study aimed to elucidate the underlying mechanisms of gastric NET formation in AIG by analyzing gastric mucosa-associated microbiota and host tissue-derived metabolite profiles. A total of 19 patients diagnosed with AIG and 12 controls uninfected with Helicobacter pylori underwent gastric mucosal biopsies for microbiome analysis using next-generation sequencing with primers targeting the V3-V4 region of the 16S rRNA gene, and metabolome analysis using capillary electrophoresis time-of-flight mass spectrometry. Microbiome analysis revealed significantly reduced α-diversity indices in patients with AIG when compared with the control group. β-Diversity analysis showed distinct microbial compositions among the control, NET-negative, and NET-positive groups. The NET-positive group exhibited a significantly higher abundance of Proteobacteria and Fusobacteriota, particularly Haemophilus parainfluenzae, Fusobacterium periodonticum, and Fusobacterium nucleatum, whereas Firmicutes, including Streptococcus salivarius and Veillonella atypica, were significantly decreased compared with the NET-negative group. Metabolome analysis revealed a shift away from glycolysis and tricarboxylic acid cycle activity toward alternative metabolic pathways in patients with AIG. Integrated analysis of gastric microbiota signatures (GMS) and tissue metabotypes demonstrated significant associations among GMS, tissue metabotypes, and NET diagnosis. These findings highlight marked shifts in gastric mucosa-associated microbiota profiles in patients with AIG who developed gastric NETs. Tissue-specific metabolic alterations may precede mucosal dysbiosis in patients with AIG and promote the development of a microenvironment implicated in NET formation.